2018
DOI: 10.18203/2349-3291.ijcp20183529
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and practices of parents about immunization of children in the age group 2-5 years

Abstract: Background: Immunization is a highly cost-effective way of reducing morbidity and mortality in children in developing countries Objectives of this study were to determine awareness of parents and immunization status of children in the age group of 2 to 5 years and study the social factors influencing immunization status of a child.Methods: A total 200 children aged 2-5 years who are attending Pediatric OPD, immunization clinic from May 2017 to April 2018 were enrolled in the present study.Results: In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Another study by Adil et al showed that the barriers for vaccination are cost and low awareness about the ill effects of non-vaccinating their children. 1,2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Adil et al showed that the barriers for vaccination are cost and low awareness about the ill effects of non-vaccinating their children. 1,2 .…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is considered to be the most cost effective means to prevent diseases from bacteria and viruses. Immunization curtails the morbidity and mortality rate to a greater extent 1 . But according to the estimates, 25 million children and 50 million pregnant women are not receiving routine immunizations thereby almost 2 million people worldwide are dying from vaccine preventable diseases like rubella, tetanus, mumps, diphtheria, pertussis and poliomyelitis 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with similar campaigns conducted nationally and internationally: Demographic variables like literacy and religion associated with nonimmunization in study carry out Canton of Aargau, Switzerland (6) , similarly MMR immunization carried out in Bhutan (7) . Parents hesitance to immunization is due to overlook of vaccination card and not aware of proper vaccination schedule (8) . Higher proportion of employed mothers able to show fully immunization to their children due to better understanding of importance of elimination of diseases (9) .Another review of study carried out Pune suggests mass media campaign and continuous IEC strategies increases the knowledge quotient among women and school children which will contribute in long term foe better healthy society (10) .…”
Section: Discussionmentioning
confidence: 99%
“…The results are similar to Upadhye JV et al Mathew Joseph L18 systematic review and Kumar et al studies. 22,24 Obstacles to immunization like mother too busy with work, child ill; mother ill, family problem and shifting of residence are noted in 57% (n=45) of partially immunized children. The second common reason identified is no motivator and postponing immunization until a favorable time with 32.9% (n=26) children being affected.…”
Section: Discussionmentioning
confidence: 99%